Studi Literatur Hak-Hak Hukum Dan Upaya Hukum Perlindungan Anak Korban Kejahatan - Prakasa, Nugraha Medica; Aransyah, Ade (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Children are considered the hope of the nation in the future, and they have rights that must be guaranteed. Child protection is all activities to ensure and protect children and their rights so that they can live, grow, develop, and participate optimally in accordance with their human dignity, and receive protection from violence and discrimination, this study aims to describe the legal rights and legal efforts of child victims of crime in legal studies. The results of the research Legal rights and legal remedies for the protection of child victims of crime. The protection of child victims of crime must adopt a holistic approach that not only considers the legal needs, but also the physical, emotional, and psychological needs of children. Restorative justice also provides an influence in the efforts of legal protection rights of children emphasizing the importance of restoring the damage caused by crime